(untitled) (International Journal of Nursing Education, 2020)
Home Accidents have been identified as the largest single cause of death after the age of one year and areamong the most severe health problems facing the world today. Keeping the toddler safe is a major priorityfor parents. Kid source online categories about toddler’s accidents were home safety from poisoning,electrical appliances, environmental safety from fall and drowning and safety play from injurious toys.Injury prevention at home is an important concern of parents of toddlers. situations that can result in injuryIn both the industrialized world and developing countries, accidents remain one of the major five leadingcauses of death. The objective of the study was to assess the level of knowledge regarding prevention ofdomestic accidents A quantitative approach with descriptive research design was selected for the study. 50number of mothers were selected by convenience sampling techniques from paediatric OPD. After obtainingthe permission from institutional authority the consent from the mothers were taken the knowledge wasassessed by using a self administered structured questionnaire. The result showed that greater than 54%of mother are having average knowledge, 30% of mother having poor knowledge and 16% of mother arehaving good knowledge regarding the prevention of domestic accident.